The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/01047760201622022070
|View full text |Cite
|
Sign up to set email alerts
|

Micromorfometria Foliar De Palicourea Rigida Kunth. (Rubiaceae) Em Ambiente De Cerrado E Campo Rupestre

Abstract: MICROMORFOMETRIA FOLIAR DE PALICOUREA RIGIDA KUNTH. (RUBIACEAE) EM AMBIENTE DE CERRADO E CAMPO RUPESTRERESUMO: Este trabalho teve como objetivo um estudo anatômico descritivo e quantitativo da estrutura foliar de Palicourea rigida Kunth. (Rubiaceae), espécie que ocorre em áreas de cerrado e campo rupestre. As observações anatômicas foram realizadas em folhas de material fresco ou fixado, tratadas segundo metodologias usuais em anatomia vegetal. Foram observadas as seguintes características: epidermes do pecíol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…All of the studied species present a thickening in the periclinal walls of the ordinary epidermal cells; a feature that is also found in other plants from high altitudes (Körner et al 1989;Gavilanes et al 2016). Such thickening can be an adaptation to the environmental conditions present at high altitudes, serving as a filter to reflect or absorb the high UV-radiation (Robberecht et al 1980), thus compensating for the thin cuticle layer observed in all of the studied species.…”
Section: Ecological Interpretationsupporting
confidence: 69%
See 1 more Smart Citation
“…All of the studied species present a thickening in the periclinal walls of the ordinary epidermal cells; a feature that is also found in other plants from high altitudes (Körner et al 1989;Gavilanes et al 2016). Such thickening can be an adaptation to the environmental conditions present at high altitudes, serving as a filter to reflect or absorb the high UV-radiation (Robberecht et al 1980), thus compensating for the thin cuticle layer observed in all of the studied species.…”
Section: Ecological Interpretationsupporting
confidence: 69%
“…In addition to its contribution to taxonomy and systematics, the knowledge of plant anatomy can be useful for identifying local adaptations, when the environmental context is considered (e.g., Starr 1912;Hayden 1919;Metcalfe and Chalk 1979;Morretes 1980;Mott and Michaelson 1991;Somavilla and Graciano-Ribeiro 2011;Aguiar-Dias et al 2012;Jakovljevic ´et al 2014;Sanso et al 2014;Perrone et al 2015;Gavilanes et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some species demonstrated grouped stomata (described as twinned stomata by Accorsi [1947]) or malformed subsidiary cells; those finding agree with the studies of Mantovani et al (1995) and Gavilanes et al 2016. Accorsi (1947 reported the presence of twinned stomata in 39.45% of a total of 601 Rubiaceae species.…”
Section: Discussionsupporting
confidence: 87%